Corruption and Village: Accountability of Village Fund Management on Preventing Corruption (Problems and Challenges) - Ash-shidiqqi, Ellectrananda Anugerah; Wibisono, Hindrawan (Faculty of Law, Universitas Negeri Semarang, 2018)
Village funds have not been used optimally for village development. Some cases of misappropriation of village funds occur due to a lack of accountability in the use of village funds as well as the lack of supervision from related parties. The lack of competency in the use of village funds is also the reason for the occurrence of cases of abuse and corruption of village funds. This study focuses on aspects of accountability and supervision of village funds using literature. The results of this study produce an ideal model of accountability for the use of village funds ranging from supervision to use so that the village is expected to be more maximal in using village funds for development.